Yoga sebagai upaya perbaikan fungsi kognitif pada lansia - Halimsetiono, Elita (JURNAL KESEHATAN PRIMER, 2023)
Introduction: The gradual changes that occur in the elderly, even though it is a normal process, will cause a decrease in their functions and abilities. One of the decreased functions that can affect the quality of life of the elderly is a decrease in cognitive function, where this decrease will have an impact on the emergence of dependency in the elderly due to their inability to carry out daily activities. This article aims to provide an overview of yoga as an effort to improve cognitive function in the elderly. Methods: This article is a literature review with data sources from national and international journals which were searched through the Google Scholar database using the keywords yoga, cognitive function, and elderly. The inclusion criteria were in the form of research articles in Indonesian or English which are available in open-access and full-text journals published in 2012-2022. From the search results, five research articles were found that met the inclusion criteria and contained the theme of yoga as an effort to improve cognitive function in the elderly. The articles were then reviewed to get a precise and comprehensive conclusion about the description of yoga. Results: Yoga can significantly improve cognitive function in the elderly, and can increase the volume of the bilateral hippocampus and the thickness of the left prefrontal cortex which play a role in the learning process, executive function, and memory of the elderly. Conclusion: Yoga has benefits for improving cognitive function in the elderly, so yoga can be considered as a way to maintain cognitive function in the elderly.